Towards a revision of the moss genus Fissidens (Fissidentaceae) in Peninsular Malaysia - Syazwana, Nur; Norhazrina, Nik; Maideen, Haja; Yong, Kien Thai; Suleiman, Monica (Malaysian Nature Society, 2018)
Fissidens Hedw. Is characterized by distichous leaves which are vertically placed, differentiated into a vaginant lamina consisting of two lamellae that clasp the stems, a dorsal lamina which is located opposite of the vaginant lamina, and an apical lamina above the vaginant lamina, peristome teeth split into two up to middle, with longitudinal stripes. At present, 28 species of Fissidens have been recognized in Peninsular Malaysia. This paper is based on evaluation of all the characters used to circumscribe the genus and the species from Peninsular Malaysia. Features which are useful for distinguishing species within the genus such as the characters of leaves, limbidium, lamina cell, costa, axillary hyaline nodule, seta and plant sexuality are being carefully examined.